2020
DOI: 10.1620/tjem.250.233
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Remodeling Biomarkers as Potential Circulating Markers of Left Ventricular Hypertrophy in Heart Failure with Preserved Ejection Fraction

Abstract: Soluble suppressor of tumorigenicity 2 (sST2), galectin-3, growth differentiation factor (GDF)-15 and syndecan-1 represent biomarkers of cardiac remodeling, involved in heart failure (HF) progression. We hypothesize that their plasma concentrations, together with brain natriuretic peptide (BNP), are different in HF stratified by ejection fraction (EF), demonstrating correlations with echocardiographic parameters that indicate left ventricular (LV) hypertrophy; LV mass index (LVMI) and posterior wall and septum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 26 publications
1
7
0
1
Order By: Relevance
“…To measure galectin-3 concentration in circulation, three studies (6,7,15) used Abbot Laboratories' Architect System, one study (12) used a human galectin-3 assay kit , another (2) used a Quantikine USA kit, and the rest all used enzyme-linked immunosorbent assays (ELISAs) from various manufacturers. Detailed galectin-3 measurement information, including storage temperature and storage duration (where provided), is shown in Table 4.…”
Section: Discussionmentioning
confidence: 99%
“…To measure galectin-3 concentration in circulation, three studies (6,7,15) used Abbot Laboratories' Architect System, one study (12) used a human galectin-3 assay kit , another (2) used a Quantikine USA kit, and the rest all used enzyme-linked immunosorbent assays (ELISAs) from various manufacturers. Detailed galectin-3 measurement information, including storage temperature and storage duration (where provided), is shown in Table 4.…”
Section: Discussionmentioning
confidence: 99%
“…The blockage of upregulated galectin-3 was found to decrease cardiovascular fibrosis and inflammation in a diet-induced obesity animal model [ 21 ]. In heart failure, systemic IL-33 R and galectin-3 were described as markers of left ventricular hypertrophy with reduced ejection fraction [ 22 , 23 ], as well as independent predictors for ischemia [ 24 ]. In the present study, galectin-3 showed no correlation with troponin T concentrations in polytrauma patients, but was significantly increased in the group of patients with troponin T levels ≥50 pg/mL compared to patients without a clinically relevant troponin T concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac overload and myocardial cell injury can lead to reduced cardiac function, which results in compensatory changes such as ventricular hypertrophy and chamber enlargement, as well as corresponding changes in cardiomyocytes, extracellular matrix, and collagen fiber networks followed by ventricular remodeling, leading to further deterioration of cardiac function ( 18 ). Multiple factors are involved in the progression of HF, such as myocardial necrosis, apoptosis, autophagy, fibrosis, oxidative stress, inflammatory response, and neurohumoral regulatory disorders, as well as changing levels in a series of biomarkers ( 19 ). The American College of Cardiology/American Heart Association/Heart Failure Society of America (ACC/AHA/HFSA) guidelines released in 2017 stated that BNP and NT-proBNP provide clear diagnostic value in patients with chronic HF ( 20 ).…”
Section: Discussionmentioning
confidence: 99%